Investigation of antibacterial mechanism and identification of bacterial protein targets mediated by antibacterial medicinal plant extracts - Yong, A.L.; Ooh, K.F.; Ong, H.C.; Chai, T.T.; Wong, F.C. (Elsevier, 2015)
In this paper, we investigated the antibacterial mechanism and potential therapeutic targets of three antibacterial medicinal plants. Upon treatment with the plant extracts, bacterial proteins were extracted and resolved using denaturing gel electrophoresis. Differentially-expressed bacterial proteins were excised from the gels and subjected to sequence analysis by MALDI TOF-TOF mass spectrometry. From our study, seven differentially expressed bacterial proteins (triacylglycerol lipase, N-acetylmuramoyl-l-alanine amidase, flagellin, outer membrane protein A, stringent starvation protein A, 30S ribosomal protein s1 and 60 kDa chaperonin) were identified. Additionally, scanning electron microscope study indicated morphological damages induced on bacterial cell surfaces. To the best of our knowledge, this represents the first time these bacterial proteins are being reported, following treatments with the antibacterial plant extracts. Further studies in this direction could lead to the detailed understanding of their inhibition mechanism and discovery of target-specific antibacterial agents.